2023
DOI: 10.3389/fendo.2023.1172199
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein-7 attenuates pancreatic damage under diabetic conditions and prevents progression to diabetic nephropathy via inhibition of ferroptosis

Abstract: BackgroundApproximately 30% of diabetic patients develop diabetic nephropathy, a representative microvascular complication. Although the etiological mechanism has not yet been fully elucidated, renal tubular damage by hyperglycemia-induced expression of transforming growth factor-β (TGF-β) is known to be involved. Recently, a new type of cell death by iron metabolism called ferroptosis was reported to be involved in kidney damage in animal models of diabetic nephropathy, which could be induced by TGF-β. Bone m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…Therefore, further investigation of the ferroptotic biomarkers has broad prospects for performing targeted therapies in kidney diseases. With advances of studies, many new regulators related to ferroptosis have been confirmed, such as ACSL4 61 , bone morphogenetic protein-7 (BMP7) 164 and ZRT/IRT-like protein 14 (ZIP14) 126 , which will further promote the understanding of the regulatory mechanism of ferroptosis and provide promising directions for expanding novel drugs for the treatment of kidney diseases in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, further investigation of the ferroptotic biomarkers has broad prospects for performing targeted therapies in kidney diseases. With advances of studies, many new regulators related to ferroptosis have been confirmed, such as ACSL4 61 , bone morphogenetic protein-7 (BMP7) 164 and ZRT/IRT-like protein 14 (ZIP14) 126 , which will further promote the understanding of the regulatory mechanism of ferroptosis and provide promising directions for expanding novel drugs for the treatment of kidney diseases in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Further experiments demonstrated that N-acetylcysteine (NAC) and insulin combination therapy had an anti-ferroptosis ability in renal TEC, likely by binding Sirt3 and increasing the expression of Sirt3 and GPX4 expression while inhibiting that of sod2, indicating a novel signaling SIRT3-SOD2-Gpx4 in ameliorating DN through preserving the mitochondrial homeostasis and alleviating ferroptosis [ 49 ]. In mice RTECs, Bone morphogenetic protein-7 (BMP7), an antagonist of TGF-β, has been shown to accelerate the regeneration of pancreatic beta cells to inhibit ferroptosis through GPX4 signaling [ 50 ].…”
Section: Ferroptosis In Diabetic Nephropathymentioning
confidence: 99%